The full extent: An inquiry into nature and destiny - K.M. Delport (Acta Theologica)
Dr. K.M. Delport writes a bookreview of: Richard Botelho, (Danville: Windstream Publishing Company, 2022), pp. 282, $20.71, ISBN: 978-0-9643926-3-2